Actual issues of countering the financing of terrorism and extremism: a psychological and forensic aspect - Arenova, L.K.; Nabieva, E.A. (Bulletin of the Karaganda University “Law Series”, 2020)
The relevance of the study: The relevance of the studied problem is due to the need to consider combating the financing of terrorism, from the psychological and forensic aspects, both in Kazakhstan and at the international level as a whole. The financing of terrorism is a phenomenon that acts as the main platform for the spread of various forms of extremism and terrorism, creates a potential and real danger to economic security, political stability and the integrity of states, including Kazakhstan, its sovereignty and territorial integrity, as an independent state. The purpose of the article: is a psychological and forensic review of the aspects of financing terrorism, and a legal analysis of measures to ensure effective and timely counteraction to the financing of terrorism in Kazakhstan, identifying problematic issues of a psychological, criminalistic and legislative nature. Research Methods: The leading approach to the study of combating the financing of terrorism is the systematic-activity approach and the method of legal analysis of existing national legislation in this area. Results of the study: Psychological and criminalistic aspects and legislative regulation of countering the financing of terrorism and extremism, sanctions as a criminal act, identifying new risks for the financing of terrorism, and their impact on the formation of poliative issues in Kazakhstan, and their effective resolution are presented. Practical relevance: Based on the current national legislation of Kazakhstan, the main elements of the financing of terrorism and extremism were identified, discussion and urgent issues requiring additional legislative settlement were identified, related to both psychological and criminalistic aspects and the imposition of punishment under this criminal law norm, in the aspect of prevention crimes, identified threats and vulnerabilities associated with the financing of terrorism and extremism in Kazakhstan at the present Mr. stage.